2018
DOI: 10.1161/jaha.118.008824
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cystathionine and Risk of Incident Stroke in Patients With Suspected Stable Angina Pectoris

Abstract: BackgroundCystathionine is an intermediate product in the transsulfuration pathway and formed during the B6‐dependent conversion of methionine to cysteine. Elevated plasma cystathionine has been related to atherosclerosis, which is a major etiological factor for ischemic stroke. However, the role of cystathionine in stroke development is unknown. Therefore, we prospectively assessed the association of circulating levels of cystathionine with risk of total and ischemic stroke.Methods and ResultsTwo‐thousand thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Our finding that serum cystathionine and tCys were associated with adverse muscle parameters in older subjects is novel, and might seem counterintuitive, since they are on the metabolic pathway from the essential SAA methionine to the key antioxidant tGSH. However, both cystathionine and tCys are emerging as biomarkers of adverse health in older subjects, including predicting type 2 diabetes [43], cardiovascular events [44], and mortality [45]. In the present study these SAAs also correlated with dietary inflammatory potential.…”
Section: Discussionsupporting
confidence: 52%
“…Our finding that serum cystathionine and tCys were associated with adverse muscle parameters in older subjects is novel, and might seem counterintuitive, since they are on the metabolic pathway from the essential SAA methionine to the key antioxidant tGSH. However, both cystathionine and tCys are emerging as biomarkers of adverse health in older subjects, including predicting type 2 diabetes [43], cardiovascular events [44], and mortality [45]. In the present study these SAAs also correlated with dietary inflammatory potential.…”
Section: Discussionsupporting
confidence: 52%
“…Cyathione is a sulfur-containing amino acid. In patients with cardiovascular disease, the increase of cyclic cystathione is related to oxidative damage and endothelial dysfunction [ 34 ]. We found that cystathionine is potentially related to DM, but the specific mechanism needs further study.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, attention was drawn to cystathionine, an intermediate product of cysteine synthesis from homocysteine by vitamin B6-dependent transsulfuration. Elevated plasma cystathionine was found to be correlated with stroke and global mortality in the context of coronary heart disease (Dhar et al 2018(Dhar et al , 2019.…”
Section: Benefits (Human Studies)mentioning
confidence: 99%